A Low cost prototype for Vehicle to Infrastructure communication (International Journal of Engineering and Computer Science, 2016)
Exchange of messages in Cooperative Communication and Sharing applications is the significant role in vehicular adhoc network(VANET)s for passengers, driver safety, warning indications, weather updates, traffic updates  and road conditions  etc can be shared among vehicle nodes in VANET within the STS (Smart Transportation Systems). We conducted an experimental setup to study and create a simple network among five vehicle nodes & it connectivity. Design of each vehicle node composed of communication unit, Processing unit, GPS and power source. Each vehicle node in network exchanges or shares details such as position, speed & direction etc. of the vehicle node to Infrastructure or RSU in which administrator or authorized user can track the mobility path record of that vehicle including current status of a vehicle. This hardware can also useful to trace any missing vehicles, theft vehicles, misbehave vehicles using latitude and longitude of vehicle. Our results showed that the Xbee wifi modules are not enough to track the high mobility vehicle without time gap.  We also observed a degradation of network performance in high way scenarios. We created the base station to log and update cloud to record the details. This application can be integrated to Internet to form the Internet of Vehicle (IoV) network which is a subclass of Internet of Everything (IoT).